Pendidikan Lintas Budaya di Era Digital: Pemanfaatan Game Roblox sebagai Media Gen Z dalam Mengurangi Steorotip dan Membangun Toleransi - Wulandari, Astria; Najamuddin, Najamuddin; Alwi, Alimin (Metta : Jurnal Ilmu Multidisiplin, 2025)
The digital era increases opportunities for cross-cultural interaction, but Generation Z is still vulnerable to cultural stereotypes and misconceptions. This study aims to analyze the use of the Roblox platform as a cross-cultural learning medium to reduce stereotypes and increase empathy. Using qualitative methods with a descriptive approach, data were obtained through in-depth interviews, participant observation, and documentation of interactions and cultural representations in the virtual world. The results show that collaborative features, real-time communication, avatar customization, and thematic world exploration in Roblox encourage cultural dialogue, reduce social distance, and reduce the tendency for negative generalizations. The gamification mechanism also increases motivation and intercultural sensitivity. The study concludes that Roblox has significant potential as an effective cross-cultural education medium for Generation Z, although its implementation requires adequate pedagogical support and technological infrastructure.